THE RELATIONSHIP BETWEEN IMPLEMENTATION OF PRIMARY NURSE ASSIGNMENT METHOD WITH PATIENTS’ SATISFACTION - Imelda - Simanjuntak; Albiner Siagian; Sri Eka Wahyuni (International Journal of Nursing and Health Services (IJNHS), 2019)
Nursing care as an integral part of health care and plays an important role to improve quality healthcare services at hospital. The study aimed to examine the relationship between implementation of primary nurse assignment method with patients’ satisfaction. A cross sectional study design was applied in this study. The findings showed that nursing orientation has strong correlation with patients’ satisfaction (RR-value = 3.64). Whereas, discharge planning was weak correlation with interpersonal communication (RR-value = 1.70). Documentation has stronger correlation with nurses’ skills (RR-value = 4.94) and supervision was weak correlation with nurses’ skill (RR-value = 1.68). This method was effective to implement wide hospital to improve patients’ satisfaction on healthcare services. Keywords: primary nurse assignment method, patients’ satisfaction